The potential of curcumin in tissue engineering and nanotechnology-based drug delivery systems: A bibliometric analysis - Ziksahna, Kaan; Adiyil, Rumeysa; Ozkan, Melisa; Ihlamur, Murat (ELSEVIER SCIENCE INC, 2025)
Introduction: Curcumin is widely investigated in tissue engineering and nanotechnology-enabled drug delivery, yet the rapidly expanding literature lacks a consolidated map to guide translation. To address this gap, we mapped global output, hotspots, and collaboration patterns on curcumin and aligned bibliometric trends with translational needs. Methods: We conducted a Scopus-based bibliometric analysis of records published between 1997 and 2024 using a single-day snapshot (21 February 2025). A reproducible TITLE-ABS-KEY query centered on curcumin retrieved 12,327 documents. After retrieval, de-noising retained records that mentioned curcumin (or variants) in the title, abstract, or author keywords. We computed standard indicators (outputs, citations, subject areas, countries, institutions, authors, journals) and constructed keyword co-occurrence and collaboration networks in VOSviewer. Results: Outputs increased sharply after 2016 and concentrated on pharmacology, biochemistry, materials science, and engineering. China (28.1 %), India (21.5 %), and the United States (12.6 %) led publication counts. Recurrent hotspots included bioavailability/controlled release, apoptosis/reactive oxygen species (ROS), hydrogels/nanofibers, and neuroprotection. Collaboration maps showed dense hubs around China, India, and the United States, while several regions were underrepresented. Conclusion: Hotspots mirror experimental advances with nanocarriers such as PLGA, liposomes, and dendrosomes that improve curcumin stability, uptake, and therapeutic indices. Methodological transparency (single-source justification, query disclosure, de-noising) enhances reproducibility. Translational progress will benefit from harmonized in vivo models, full formulation reporting-size, polydispersity index (PDI), zeta potential, loading, and release-Good Manufacturing Practice (GMP)-compatible scale-up, and region-adapted regulatory guidance.
Keywords: Curcumin; Nanotechnology; Drug delivery systems; Tissue engineering; Bibliometric analysis; BIOAVAILABILITY; NANOCARRIERS; EFFICACY; Integrative & Complementary Medicine